TINJAUAN LITERATUR: Pendidikan Entrepreneur Mahasiswa - Praditya, Alvin; Pamungkas, Ibrahim Bali; Rodiyana, Nanda (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
The purpose of this research is to identify and direct efforts needed to enhance the role of higher education institutions in entrepreneurship education. The method for searching data sources for articles was conducted through the GARUDA database (2019-2023) to retrieve relevant articles published in Bahasa Indonesia. Terms and key phrases related to student entrepreneurs were reviewed through abstracts or texts of research journals before being included in the review according to criteria. Based on the analysis of the literature review, there were 59 relevant journals found. The review results indicate that by implementing relevant curriculum provision steps, business incubators and startup accelerators, entrepreneurship skills training, collaboration with industries, funding support, entrepreneurship mindset development, and coaching and mentoring programs, universities are expected to play a more effective role in preparing students to become successful entrepreneurs. This, in turn, will contribute to economic growth, job creation, and achieving Indonesia's vision as a developed country by 2045.